Effects of pregnancy on chronic urticaria: Results of the PREG‐CU UCARE study. Issue 10 (12th June 2021) - Kocatürk, Emek; Al‐Ahmad, Mona; Krause, Karoline; Gimenez‐Arnau, Ana M.; Thomsen, Simon Francis; Conlon, Niall; Marsland, Alexander; Savk, Ekin; Criado, Roberta F.; Danilycheva, Inna; Fomina, Daria; Godse, Kiran; et al.
Abstract: Background: Chronic urticaria (CU) predominantly affects women, and sex hormones can modulate disease activity in female CU patients. As of now, the impact of pregnancy on CU is largely unknown. Aim: To analyze the course and features of CU during and after pregnancy. Patients and methods: PREG‐CU is an international, multicenter study of the Urticaria Centers of Reference and Excellence (UCARE) network. Data were collected via a 47‐item questionnaire completed by CU patients, who became pregnant within the last 3 years. Results: A total of 288 pregnancies of 288 CU patients from 13 countries were analyzed (mean age at pregnancy: 32.1 ± 6.1 years, duration of CU: 84.9 ± 74.5 months; CSU 66.9%, CSU + CIndU 20.3%, CIndU 12.8%).During pregnancy, 51.1% of patients rated their CU as improved, 28.9% as worse, and 20.0% as unchanged.CU exacerbations most commonly occurred exclusively during the third trimester (in 34 of 124 patients; 27.6%) or the first (28 of 124; 22.8%). The risk factors for worsening of CU during pregnancy were having mild disease and no angioedema before pregnancy, not taking treatment before pregnancy, CIndU, CU worsening during a previous pregnancy, treatment during pregnancy, and stress as a driver of exacerbations. After giving birth, urticaria disease activity remained unchanged in 43.8% of CU patients, whereas 37.4% and 18.1% experienced worsening and improvement, respectively. Conclusions: These results demonstrate the complex impact of pregnancy on the course of CU and help to better counsel patients who want to become pregnant and to manage CU during pregnancy. Abstract : During pregnancy, 51.1% of patients rated their CU as improved, 28.9% as worse, and 20.0% as unchanged; rate of angioedema decreased from 38.2% to 17.4%. CU exacerbations occurred most commonly in the third trimester (27.6%) or in the first trimester (22.8%). Of the patients whose urticaria improved during pregnancy, 50% experienced worsening after giving birth, whereas 33.6% and 16.4% reported no change. Abbreviations: CIndU, chronic inducible urticaria; CU, chronic urticaria; PREG‐CU, Pregnancy and Chronic Urticaria; UCARE, Urticaria Centers of Reference and Excellence